Comparison of In Vitro and In Vivo MRI of the Spine Using Parallel Imaging - Ruel, Lucile; Brugieres, Pierre; Luciani, Alain; Breil, Stephane; Mathieu, Didier; Rahmouni, Alain (American journal of roentgenology (1976), 2004)
The purpose of this study was to compare the image quality of two parallel-imaging methods applied to standard turbo spin-echo T2-weighted imaging of the lumbar spine. Phantom imaging and lumbar spine studies of 15 healthy subjects were performed using T2-weighted turbo spin-echo sequences obtained with and without parallel imaging (generalized autocalibrating partially parallel acquisition [GRAPPA] and modified sensitive encoding [mSENSE]) on a 1.5-T magnet. The signal-to-noise ratio (SNR) and uniformity were measured in the phantom, and SNR and signal difference-noise ratio were evaluated in cerebrospinal fluid, vertebral bodies, and subcutaneous fat of the volunteers, using both techniques sequentially. Aliasing artifacts on GRAPPA and mSENSE images were visually evaluated. SNRs were compared using the Student's paired t test, with p values less than 0.05 considered significant. In the phantom study, when the same number of coil elements were used (n = 3), SNR and uniformity values obtained with standard T2-weighted turbo spin-echo sequences were higher than those obtained with parallel sequences. The GRAPPA SNR obtained with three coil elements was higher than the standard T2-weighted SNR obtained with one coil element. Similar findings were noted regarding uniformity. In the lumbar spine, GRAPPA SNR values for fat, cerebrospinal fluid, and vertebral bodies were significantly higher than mSENSE SNR values, with a p value less than 0.01, but were not significantly different from T2-weighted turbo spin-echo SNR values. GRAPPA signal difference-noise ratio values were significantly higher than mSENSE signal difference-noise ratio values, with a p value less than 0.01, but were not significantly different from T2-weighted turbo spin-echo signal difference-noise ratio values. GRAPPA produced fewer aliasing artifacts than mSENSE. In spine MRI, GRAPPA may be used to reduce scanning time and yields a higher SNR than mSENSE without any increase in aliasing artifacts and with an SNR similar to that obtained with standard T2-weighted turbo spin-echo.